2012
DOI: 10.1007/s10565-012-9215-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clothianidin exposure on sperm quality, testicular apoptosis and fatty acid composition in developing male rats

Abstract: Clothianidin (CTD) is one of the latest members of the synthetic organic insecticides, the neonicotinoids. In the present study, it was aimed to investigate if daily oral administration of CTD at low doses for 90 days has any deleterious effects on reproductive functions of developing male rats. Animals were randomly divided into four groups of six rats each, assigned as control rats, or rats treated with 2 (CTD-2), 8 (CTD-8) or 32 (CTD-32) mg CTD/kg body weight by oral gavage. The significant decreases of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 62 publications
4
40
0
Order By: Relevance
“…In male rats, neonicotinoid decreased sperm motility and epididymal sperm concentration, and increased the abnormal sperm rate [2]. We found that it decreased the number of germ cells and increased DNA-fragmented germ cells in seminiferous epithelium in a dose-dependent manner, but we also found normal spermatogenesis in the treatment groups and little effect on the egg weights and the fertilization rates in females bred with the treated males.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In male rats, neonicotinoid decreased sperm motility and epididymal sperm concentration, and increased the abnormal sperm rate [2]. We found that it decreased the number of germ cells and increased DNA-fragmented germ cells in seminiferous epithelium in a dose-dependent manner, but we also found normal spermatogenesis in the treatment groups and little effect on the egg weights and the fertilization rates in females bred with the treated males.…”
Section: Discussionmentioning
confidence: 47%
“…It is reported that neonicotinoid causes DNA fragmentation of rat sperm through oxidative stress [2], and the injection of DNA-fragmented sperm into human egg cells inhibits embryo development after the eight-cell stage [18]. In addition, it is known that injury to sperm DNA after second meiosis is not repaired, and that DNA-fragmented sperm are found in human ejaculate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example; Tanaka (2012) has reported that CTD administration through diet to female mice during the gestation period has no effect on selected reproductive parameters, including litter size, litter weight, or sex ratio at birth. However, in our previous study (Bal et al, 2012a), we demonstrated that CTD exposure at the no observed adverse effect level (NOAEL) dose (32 mg/kg) daily for 90 days caused significant decreases in reproductive organ weights, sperm concentration, testicular GSH level, and significant increases in some testicular fatty acid composition, cholesterol level, apoptotic germ cells, and sperm DNA fragmentation in developing male rats. In our other study (Bal et al, 2012b), we also found that the nicotinoid, imidacloprid, when administered at NOAEL dose levels, leads to testicular dysfunction, including deteriorated sperm quality, decreased testosterone level, increased apoptotic germ cells, increased sperm DNA fragmentation, and disturbed oxidant/antioxidant balance and fatty acid composition in adult male rats.…”
Section: Clothianidinmentioning
confidence: 87%
“…However, studies (8,9) have reported genotoxic effects for Acm and other neonicotinoid insecticides (30)(31)(32)(33). For instance, Bal et al (34) reported that the neonicotinoid clothianidin induced impairment of the male mouse reproductive system. Such claims are inconsistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%